Exclusion of Madheshi Women in Decision Making - Tiwari, Sushma (Academic Voices: A Multidisciplinary Journal, 2015)
A country’s socio-economic growth cannot take place if half of its population is down-trodden. In Nepal women of every section of society are excluded in one or other form. The identity of woman comes from her own family and decision-making autonomy also should start from the household. This article is concerned with the decision-making autonomy of the Madheshi women in Parsa district. The findings reveal that still these women are almost excluded from the structure of decision making autonomy within the households. It maybe argued that the status of Madheshi women is poorer due to low education and employment, low exposure of women and less decision making autonomy. DOI: http://dx.doi.org/10.3126/av.v4i0.12361 Academic Voices Vol.4 2014: 68-72